Critical Perspectives on Cultural Memory and Heritage Construction, Transformation and Destruction - Apaydin, Veysel (UCL Press, 2020)
Critical Perspectives on Cultural Memory and Heritage focuses on the importance of memory and heritage for individual and group identity, and for their sense of belonging. It aims to expose the motives and discourses related to the destruction of memory and heritage during times of war, terror, sectarian conflict and through capitalist policies. It is within these affected spheres of cultural heritage where groups and communities ascribe values, develop memories, and shape their collective identity. Chapters in the volume address cultural memory and heritage from six global perspectives and contexts: first, the relationship between cultural memory and heritage; second, the effect of urban development and large infrastructure on heritage; third, the destruction of indigenous heritage; fourth, the destruction of heritage in relation to erasing memory during sectarian violence and conflict; fifth, the impact of policymaking on cultural heritage assets; and sixth, a broad reflection on the destruction, change and transformation of heritage in an epilogue by Cornelius Holtorf, archaeologist and Chair of Heritage Futures at UNESCO.